Utilización del Moodle como un Entorno Personal de Aprendizaje en contexto de educación superior, una revisión de literatura. - Tusa Jumbo, Fernanda (2015)
Inside the topic Personal Environment of Institutional Learning (IPLE) this paper does an analysis about the concept virtual environment learning in order to answer the question ¿a Moodle can be applied as virtual environment learning inside superior educational contexts? To answer this question, this paper uses the following methodology observation, data collection, comprehensive lecture of texts, conceptual framing and mental maps of content organization. Similarly, this paper does a literature review by indexed journals, articles and digital libraries. Also this research work employs the technique of comparison hire inside multiples virtual learning environments with the objective to apply the Moodle approach. As result this article proposes a substantive theory that involves the interface’s design improvement to a graphic level taking into account the variables, information distribution, visibility and content organization about the IPLE and Moodle concepts. Finally, this article suggests that an IPLE must be applied in all superior educational contexts due to its gratuity service, tools and personal interaction level that promote these virtual environments pedagogical perspective technology perspective.